Explant culture: A relevant tool for the study of telocytes - Sanches, Bruno D. A. (2020)
Telocytes are cells present in the stroma of various tissues including the prostate. The detection of telocytes is still very much dependent on obtaining ultrastructural data that show the presence of telopodes, which are cytoplasmic projections that alternate between dilated regions, the podoms, and thin segments, the podomers. These structures are the distinctive characteristics of the telocytes. Thus, in vitro assays are important for the study of telocytes, which are more easily identified in culture, which also enables the experimental manipulation of these cells. The isolation of telocytes per se does not allow the analysis of the behavior of these cells in relation to other cell types in a given organ. In this sense, in the prostate, explants could be a useful tool for the study of telocytes. The present study obtained prostatic explants and evaluated the influence of recombinant proteins, scattering factor (SCF) and stromal-derived factor 1 (SDF-1), which could impact on the migration of CD34-positive cells. Telocytes migrate out of explants and SDF-1 stimulates the proliferation and formation of telocyte networks in vitro. Telocytes are not smooth muscle cell progenitors in the prostate; on the contrary, they are CD90- and CD44-negative cells and, hence, have limited progenitor capacity. The present study demonstrated that explants are useful tools to elucidate the nature of telocytes and their functions.